Изменения миелограммы животных после облучения с последующей коррекцией ксеногенной цереброспинальной жидкостью - Пикалюк, В.С.; Абсеттарова, А.И.; Шаймарданова, Л.Р. (Таврический медико-биологический вестник, 2013)
Метою цього дослідження було вивчення вікових морфофункціональних показників аплазованного кісткового мозку при корекції ксеногенної цереброспінальної рідиною (КЦСР). Після введення КЦСР опроміненим тваринам, відмінності в мієлограмі почали спостерігати з 5–7 доби, що свідчить про її вплив на самі ранні ланки гемоцітопоеза. Першим реагував на КЦСР еритроїдний росток, потім лімфо-і гранулоцитарний ростки. КЦСР дорослого донора надає найкращу стимулюючу дію на 3 групу реципієнтів (зрілий репродуктивний вік). У цих тварин на 21‑у добу після інфузій КЦСР цитоз збільшувався у всіх ростках гемоцітопоеза, причому найбільше в еритроцитарному – на 58,30 %, в мегакаріоцитарному – на 47,00 %. Число гранулоцитів перевищувало значення в контролі на 33,32 %. Виявилося, що КЦСР в якості коректора має позитивний вплив на всі стадії розвитку клітин КМ – бластні, проліферуючі і диференцуючи. Отримані результати будуть використані для розробки нового біологічного препарата на основі КСМР щодо попередження тяжких наслідків радіаційного опромінення як медичного, так і випадкового походження. The goal of the study was to examine the age-related morphological and functional indices of the aplastic bone marrow after the correction by the xenogenic cerebrospinal fluid (XCSF). After the injections of the XCSF to irradiated animals, the differences in the myelogram were observed from the 5th‑7th day, that indicated its effect on the earliest stages of haemopoesis. The priority directions of BM cellularity restoring were the red blood cells and lymphocytes, and then all the remaining. XCSF from the adult donor had the best stimulating effect on the third group of recipients (mature reproductive age). The adult rats on the 21‑st day after the infusion of the XCSF the cellularity was increased more in erythroid line – by 58.30 %, and in megakaryocytes line – by 47.00 %, compared to the control group. The granulocytes number after correction with the XCSF was 33.32 % higher than the value in the control group. It appears that using of the XCSF as the correcting substance has a positive impact on all stages of maturating of the bone marrow cells – blasts, proliferating and differentiating cells. The obtained results will be used to develop a new biological drug on the base of the XCSF for preventing the severe outcomes after the radiation exposure, both of medical or accidental origin.